The Role of TikTok in Shaping Gen Z's Brand Loyalty and Consumer Behavior - Andri Catur Trissetianto; Hapzi Ali (Greenation Publisher, 2025)
This study explores the impact of TikTok on Generation Z's brand loyalty and consumer habits. With the rise of social media influencers and viral marketing campaigns on the platform, TikTok has become a powerful tool for brands to connect with younger consumers. By analyzing the content and engagement levels on TikTok, this research aims to uncover the ways in which the platform shapes Gen Z's purchasing decisions and brand preferences. Through surveys and interviews with Gen Z users, this study will also examine how TikTok influences their perceptions of authenticity and trustworthiness in brands. By understanding the role of TikTok in shaping consumer habits, marketers can better tailor their strategies to effectively reach and engage with this influential demographic. Ultimately, the findings of this research will provide valuable insights for brands looking to build long-lasting relationships with Gen Z consumers in the ever-evolving digital landscape.